Cross-coupled intelligent control for a novel two-axis differential micro-feed system. (June 2018) - Du, Fuxin; Feng, Xianying; Li, Peigang; Wang, Jiawei; Wang, Zhaoguo; Yu, Chen
Nonlinear friction in a conventional drive feed system feeding at low speed is a main factor that contributes to feed drive complexity. A novel two-axis differential micro-feed system is developed in this study to overcome the accuracy limitation of conventional drive feed system. Instead of the screw-rotating-type ball screw adopted in conventional drive feed system, the transmission component of the proposed two-axis differential micro-feed system is a nut-rotating-type ball screw. In this setup, not only the screw but also the nut is driven by a servo motor. By superposing the two high-speed rotary motions (motor–drive–screw and motor–drive–nut) with an equivalent high velocity and the same rotating direction through the novel transmission mechanism, the nonlinear disturbance from the ball screw can be reduced significantly. In addition, both the axes can avoid the creeping transition zone when the table makes a zero-velocity crossing. Note that the motor load switches when the feeding direction of the table is changed, and the nonlinear friction of the table needs to be compensated. Based on this observation, we further present a cross-coupled intelligent second-order sliding mode control that includes a cross-coupled technology, a second-order sliding mode control, a wavelet fuzzy neural network estimator for the friction, and a motor load switch to improve system performance. The proposed cross-coupled intelligent second-order sliding mode control architecture is deployed on a two-axis differential micro-feed system, where numerical simulations and experiments demonstrate excellent tracking performance and friction compensation capability, achieving position tracking error reduced by 45% compared with conventional drive feed system.